Stereoselective syntheses of (+)-alpha- and (-)-beta-conhydrine from L-aspartic acid - Pandey, SK; Kumar, P (Tetrahedron Letters, 2005)
An efficient synthesis of (+)-alpha-conhydrine 1 and (-)-beta-conhydrine 2 has been achieved by. diastereo selective alkylation of an amino aldehyde derivative 7 with ethylmagnesium bromide or diethylzinc. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkylation; conhydrine; Grignard reaction; Piperidine alkaloids; stereoselectivity

4-Formylazetidin-2-one as a useful building block for the formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine - Kale, Ajaykumar S.; Sakle, Prathmesh S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
Stereoselective formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine is described starting from an enantiopure formyl-substituted P-lactam. Grignard reaction of the N-Boc-protected-beta-lactam carbonyl group, followed by further transformations, provides a common intermediate for xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine.
Keywords: azetidin-2-one; beta-lactam; Grignard reaction; Phytosphingosine; Sphingosine

Efficient total synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid - Pandey, Satyendra Kumar; Kumar, Pradeep (European Journal of Organic Chemistry, 2007)
An efficient enantioselective synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid (1) from epichlorohydrin is described. The key steps include Jacobsen's HKR, Sharpless asymmetric dihydroxylation, regioselective opening of epoxide and cyclic sulfate. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: cyclic sulfate; Dihydroxylation; Grignard reaction; hydroboration-oxidation; Jacobsen's hydrolytic kinetic resolution (HKR); regio selectivity

Practical synthesis of (+/-)-venlafaxine - Chavan, Subhash P.; Khobragade, Dushant A.; Thakkar, Mahesh; Kalkote, Uttam R. (Synthetic Communications, 2007)
A practical total synthesis of antidepressant (+/-)-venlafaxine is disclosed.
Keywords: antidepressant; Grignard reaction; Michael addition

Stereoselective synthesis of 3-alkylidene/alkylazetidin-2-ones from azetidin-2,3-diones - Tiwari, Dharmendra Kumar; Shaikh, Ashif Y.; Pavase, Laxmikant S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2007)
Azetidin-2,3-diones have been used as synthons for the synthesis of C-3 alkylidene/alkylazetidin-2-ones. Some of the 3-alkylazetidin-2-ones are well known for their cholesterol absorption inhibitor activity. A regio and stereoselective Grignard reaction on a keto group followed by dehydration using PPh3/CCl4 reagent is a key step in this synthesis. Hydrogenation of the 3-alkylideneazetidin-2-ones provided stereoselectively cis-3-alkylazetidin-2-ones in very good yields. (c) 2006 Published by Elsevier Ltd.
Keywords: 3-diones; azetidin-2; azetidin-2-ones; beta-lactam; Grignard reaction

Concise synthesis of protected (2S,4R)-4-hydroxyornithine - Pandey, Satyendra Kumar; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2008)
A short synthesis of the nonproteinogenic amino acid, (2S,4R)-4-hydroxyornithine is described. Starting from racemic benzyl glycidol, the scaffold of the target compound was constructed in high enantio- and diastereoselectivity using Jacobsen's hydrolytic kinetic resolution (HKR) and regioselective opening of an epoxide as key steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Epoxide; Grignard reaction; hydroxyornithine; Jacobsen's HKR; Natural product

Stereoselective synthesis and antimicrobial activity of steroidal C-20 tertiary alcohols with thiazole/pyridine side chain - Shingate, Bapurao B.; Liazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2011)
Stereoselective synthesis of novel steroidal C-20 tertiary alcohols with thiazole and pyridine side chain using Grignard reaction of steroidal ketones and thiazole/pyridine magnesium bromide have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: antibacterial activity; Antifungal activity; Grignard reaction; Steroid side chain; Steroidal ketones

Stereoselective synthesis of subincanadine alkaloids framework - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
Starting from, N-tosyltryptamine and (S)-acetoxysuccinic anhydride, a facile synthesis of (-)-indolizinoindolone has been demonstrated as a basic structural outline of bioactive subincanadine alkaloids. Regioselective Grignard reaction with (S)-acetoxysuccinimide, stereoselective intramolecular cyclization to form (-)-indolizinoindolone skeleton and TiCl4 induced condensation with acetaldehyde for stereoselective generation of exocyclic carbon carbon double bond are the key features.
Keywords: (S)-Acetoxysuccinimide; alane reduction; condensation; Grignard reaction; indolizinoindolone; PCC-oxidation; stereoselective Pictet-Spengler cyclization

Synthesis of 2-azabicyclo[m.n.0]-alkanes and their application towards the synthesis of strychnos and stemona classes of alkaloids - Majumder, Binoy; Pandey, Ganesh (European Journal of Organic Chemistry, 2020)
2-Azabicyclo[m.n.0]alkane ring systems, the conceptual precursors towards the synthesis of Strychnos and Stemona classes of alkaloids, were synthesized from tert-butyl 2-(phenylsulfonyl)-7-aza-bicyclo[2.2.1]hept-2-ene-7-carboxylate by alkyl Grignard reaction and intramolecular cyclisation of the in situ generated ring opening product 2. The synthesized cis-hexahydroindole 3 and cis-octahydro-benzo[b]azepine 5 scaffolds were utilized to construct the advanced intermediates 25 and 35, respectively, towards the synthesis of the corresponding Strychnos and Stemona classes of alkaloids.
Keywords: alkaloids; amines; Grignard reaction; Michael addition; Natural products

Continuous flow telescopic synthesis of 3-methoxy propiophenone by the grignard reaction - Wankhede, Pranali; Kulkarni, Amol A. (Organic Process Research & Development, 2025)
The synthesis of 3-methoxypropiophenone 1, a crucial intermediate in the production of the analgesic tapentadol hydrochloride, was investigated using a multistep continuous flow process. The approach is based on the Grignard reaction. A series of continuously stirred tank reactors (CSTRs) were employed: the first reactors facilitated the continuous generation of Grignard reagents 3, which then reacted with propionitrile in the next CSTR to yield 1. This was followed by quenching, neutralization, and phase separation, conducted under varying temperatures and residence times. When compared to a 50% yield from an optimized batch synthesis protocol, a continuous flow synthesis helped achieve an 84% yield of the desired product in a much shorter reaction time. A kinetic model was developed to predict the Grignard reagent formation and product yield, revealing that the mass transfer effect is insignificant at a higher stirring rate. The approach is highly scalable for the synthesis of pharmaceutical intermediates.
Keywords: batch and continuous reaction; flow chemistry; Grignard reaction; heterogeneous kinetics